2019
DOI: 10.1186/s12864-019-6031-4
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ-based quantitative proteomic and physiological analysis of the response to N deficiency and the compensation effect in rice

Abstract: Background The crop growth compensation effect is a naturally biological phenomenon, and nitrogen (N) is essential for crop growth and development, especially for yield formation. Little is known about the molecular mechanism of N deficiency and N compensation in rice. Thus, the N-sensitive stage of rice was selected to study N deficiency at the tillering stage and N compensation at the young panicle differentiation stage. In this study, a proteome analysis was performed to analyze leaf differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…To further explore how rice responds to low light stress, proteins with fold change (FC) > 1.2 and p-value< 0.05 were considered as upregulated, while those with FC < 5/6 and p-value< 0.05 were considered as downregulated. These cutoffs were chosen according to a previous iTRAQ proteomic analysis on rice (Xiong et al 2019). Comparison between CL and LL revealed 1221 DEPs including 223 upregulated and 998 downregulated proteins (Table 1 and Supplemental Table 3).…”
Section: Functional Analysis Of Differentially Expressed Proteins (Deps)mentioning
confidence: 99%
“…To further explore how rice responds to low light stress, proteins with fold change (FC) > 1.2 and p-value< 0.05 were considered as upregulated, while those with FC < 5/6 and p-value< 0.05 were considered as downregulated. These cutoffs were chosen according to a previous iTRAQ proteomic analysis on rice (Xiong et al 2019). Comparison between CL and LL revealed 1221 DEPs including 223 upregulated and 998 downregulated proteins (Table 1 and Supplemental Table 3).…”
Section: Functional Analysis Of Differentially Expressed Proteins (Deps)mentioning
confidence: 99%
“…The labeled peptides were subjected to a nanospray Flex source and analyzed by a Q-Exactive mass spectrometer (Thermo, USA). The following analyses were performed according to the procedures as described by Xu et al [91] and Xiong et al [92].…”
Section: Mass Spectrometry (Ms) Analysismentioning
confidence: 99%
“…Among them, nitrogen (N) is one of the main elements of amino acids, chlorophyll, nucleic acids, lipids and many intermediate metabolites. N plays an important role in plant growth and agricultural production ( Xiong et al., 2019c ), further affecting the enrichment of root microorganisms. Studies have shown that compared with no N fertilizer treatment, N application causes the N-fixing bacterial community in rice roots to aggregate and significantly increases the relative abundance of Methylosinus in rice roots ( Liu et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the overall response of the bacterial microbiota to drought stress is taxonomically consistent across soils and cultivars and is primarily driven by an enrichment of multiple Actinobacteria and Chloroflexi, as well as a depletion of several Acidobacteria and Deltaproteobacteria (Santos-Medell谋艅 et al, 2017). The energy metabolism pathway, carbon fixation in the photosynthetic organism pathway, carbohydrate metabolic process, and reactive oxygen species metabolic process functions have a certain correlation with drought stress (Xiong et al, 2019a).…”
mentioning
confidence: 99%